1983
DOI: 10.1128/aem.45.2.428-435.1983
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Natural Microbial Communities to Degradation of Xenobiotic Compounds: Effects of Concentration, Exposure Time, Inoculum, and Chemical Structure

Abstract: Adaptation of microbial communities to faster degradation of xenobiotic compounds after exposure to the compound was studied in ecocores. Radiolabeled test compounds were added to cores that contained natural water and sediment. Adaptation was detected by comparing mineralization rates or disappearance of a parent compound in preexposed and unexposed cores. Microbial communities in preexposed cores from a number of freshwater sampling sites adapted to degrade p-nitrophenol faster; communities from estuarine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(93 citation statements)
references
References 8 publications
4
86
2
1
Order By: Relevance
“…In contrast to previous works (Spain & VanVeld, 1983;Johnsen & Karlson, 2005), consortium BOS08 did not require pre-exposure to PAHs to induce microbial adaptation and consequently degradation of those pollutants.…”
Section: Pah Degradation Capability Of Bacterial Consortiamentioning
confidence: 63%
“…In contrast to previous works (Spain & VanVeld, 1983;Johnsen & Karlson, 2005), consortium BOS08 did not require pre-exposure to PAHs to induce microbial adaptation and consequently degradation of those pollutants.…”
Section: Pah Degradation Capability Of Bacterial Consortiamentioning
confidence: 63%
“…These results were based on degradation in river water and on concentrations of up to 20 mg/L p-nitrophenol. Earlier studies of p-nitrophenol degradation in coastal sediments indicated that sediment preexposure affects the rate of degradation of the compounds by the sediment on reexposure [6,7]. p-Nitrophenol has been listed as priority pollutant by the U.S. Environmental Protection Agency.…”
Section: Introductionmentioning
confidence: 99%
“…Pritchard et al [19] observed that adaptation to methyl parathion by salt-marsh organisms required continuous exposure to the chemical. Spain and Van Veld [20] observed that the ability of microbial communities to degrade p-nitrophenol declined as the chemical disappeared from static microcosms. The researchers suggested that adaptation could possibly be maintained by "priming" microbial communities with small doses of test chemical but that some periodic exposure was necessary.…”
Section: Resultsmentioning
confidence: 99%